2019
DOI: 10.1002/admi.201900947
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Depth Profiling of Residual Stresses Due to Fine Surface Finishing

Abstract: Mechanical polishing is commonly used for both surface finishing and metallographic sample preparation for a broad range of materials. However, polishing causes local deformation and induces residual stress, which has an important effect on many surface phenomena. Until recently, it has not been possible to quantify the nanoscale depth variation of polishing‐induced plastic deformation (eigenstrain) and the associated residual stress. In this study, the magnitude and depth of polishing‐induced residual stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The formation of Al2O3 from the γ' phase (Ni3Al in the simplified case) results in a transformation strain of around 466 % [21], which means that the formation of these finger-like intrusions is indeed expected to cause compressive residual stress. The surface preparation prior to oxidation could also have an influence, since it has been shown recently that polishing with diamond slurry induces compressive residual stresses up to a few micrometers in depth [52]. Additionally, the current results show for the first time that the ring-core FIB-DIC technique is capable of providing depth-resolved residual stress profiles in native oxide layers with submicron thickness.…”
Section: Discussionmentioning
confidence: 62%
“…The formation of Al2O3 from the γ' phase (Ni3Al in the simplified case) results in a transformation strain of around 466 % [21], which means that the formation of these finger-like intrusions is indeed expected to cause compressive residual stress. The surface preparation prior to oxidation could also have an influence, since it has been shown recently that polishing with diamond slurry induces compressive residual stresses up to a few micrometers in depth [52]. Additionally, the current results show for the first time that the ring-core FIB-DIC technique is capable of providing depth-resolved residual stress profiles in native oxide layers with submicron thickness.…”
Section: Discussionmentioning
confidence: 62%
“…The Vanadium single crystal sample (control) shows insignificant tensile residual stress within the experimental error. A recent study has shown that mechanical polishing does not induce any significant residual stress and hence the sample can be considered as stress free [21].…”
Section: Resultsmentioning
confidence: 99%
“…The maps of stress distribution on the polished surface and fracture surfaces obtained on this basis confirm these assumptions. However, it should be emphasized that polishing the surface can significantly affect the state of internal stress [ 57 ], and the diamond suspensions of various sizes used in the polishing process may change the nature of stresses at a depth of up to several hundred nanometres [ 58 , 59 ]. This can significantly distort the information regarding the stresses that remain on the polished surface.…”
Section: Discussionmentioning
confidence: 99%